The Role of Evaluation in Democracy: Can it be Strengthened by Evaluation Standards? A European Perspective - Wolfgang Beywl (The Evaluation Center at Western Michigan University, 2006)
Evaluation should make a contribution to the further development of politics and society. Evaluation is itself a productive factor in democratic societies and is obliged to function according to its goals and rules. The general theme around this paper is to discuss possibilities to enhance the contribution that evaluation can make to foster democratic governance. I will address a very small aspect of this big issue. My perspective will be on evaluation as a profession and a community which is on the way to establishing its position in modern democracies, supported by making explicit its own standards for good evaluation practice.